Engineering Colloidal Metal-Semiconductor Nanorods Hybrid Nanostructures for Photocatalysis - Chen, Jiayi; Hao, D.; Chen, Wei; Liu, Y.; Yin, Z.; Hsu, H.; Ni, B.; Wang, A.; Lewis, Simon; Jia, Guohua (John Wiley & Sons, Ltd, 2023)
Comprehensive Summary: Emerging engineering strategies of colloidal metal-semiconductor nanorod hybrid nanostructures spanning from type, size, dimension, and location of both metal nanoparticles and semiconductors, co-catalyst, band gap structure, surface ligand to hole scavenger are elaborated symmetrically to rationalize the design of this type of intriguing materials for efficient photocatalytic applications.